CORRELATION BETWEEN STUDENT’S CURIOSITY AND SCIENCE LITERACY SKILLS WITH SCIENCE LEARNING ACHIEVEMENT IN ELEMENTARY SCHOOL - Aryani, Dian Fitra; Sartika, Septi Budi (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2024)
This research is a quantitative correlation study using an ex-post facto design to determine the correlation between student curiosity and science literacy skills with science learning achievement at Muhammadiyah 2 Sidoarjo Elementary School. There is no revelation about the correlation between students' curiosity, science literacy skills, and learning achievement at the elementary school level, so researchers are interested in conducting this research at Muhammadiyah 2 Sidoarjo Elementary School, which has implemented the Minimum Competency Assessment system for its students. The population and sample in this study were 86 students in 6th grade at Muhammadiyah 2 Sidoarjo Elementary School. Research data obtained using questionnaires and documents. Data analysis techniques used is multiple correlation analysis. Based on the results of the study obtained the conclusion there is a correlation between curiosity and science literacy skills of students with student’s science learning achievement.